Influence of the Natural and Geographical Environment on the Adaptation of the Deported People During the Great Patriotic War (on the Example of the Chechens) - Tsutsulaeva Sapiyat; Yangulbaeva Eliza (BIO Web of Conferences, 2023)
The purpose of the article is to identify the mechanisms of reproduction and transformation of the mental and behavioral aspects of traditional ethno-social practices in extreme conditions of exile and ethnic deportation of the Chechen people.The question of the influence of the geographical environment on the socio-political processes and mores of society was raised by ancient authors, but the great geographical discoveries that caused the rapid economic and socio-political development of Europe served as the historical prerequisites for the emergence of an integral concept of geographical determinism.